Animasi Dalam Pembelajaran - Utami, Dina (MAJALAH ILMIAH PEMBELAJARAN, 2011)
The usage of animation as learning aids is believed to have beenimproved students performance. Prior research, however, showsvarious results of the effectiveness of animation as a learning aids,depending on which level of learning and who the learner is. In somesituation, static graphical illustration is actually more useful thananimation. Once we decide to use animation for learning, we have tocarefully design it. Designing effective educational animation can betricky. The designer has consider several factors such as the learnercharacteristics, the format of the animation, the graphical quality, etc.In the end, animation is merely a tool, hence how we use it is highlydependant on the pedagogical goals.